Sustainable approach for catalytic green epoxidation of oleic acid with applied ion exchange resin - Mariam Abdul Rahman; Nabisab Mujawar Mubarak; Intan Suhada Azmi; Mohd Jumain Jalil (Scientific Reports, 2023)
Abstract Epoxides were primarily derived from petroleum-based sources. However, there has been limited research on optimizing the process parameters for epoxidized palm oil-derived oleic acid, resulting in its underutilization. Therefore, this study aimed to optimize the catalytic epoxidation of palm oleic acid concerning the oxirane content by applying ion exchange resin as a catalyst. Epoxidized oleic acid was produced using in-situ-formed performic acid by combining formic acid as the oxygen carrier with hydrogen peroxide as the oxygen donor. The findings revealed that the optimal reaction conditions for producing epoxidized oleic acid with the highest oxirane content were an Amberlite IR-120 catalyst loading of 0.9 g, a molar ratio of formic acid to oleic acid of 1:1., and a molar ratio of hydrogen peroxide to oleic acid of 1:1.1. By employing these optimal conditions, the maximum relative conversion of palm oleic acid to oxirane was achieved at 85%. The reaction rate constants (k) based on the optimized epoxidized oleic acid are determined as follows: k11 = 20 mol L−1 min−1, k12 = 2 mol L−1 min−1, and k2 = 20 mol L−1 min−1. The findings validated the kinetic model by showing good agreement between the simulation and experimental data.